2019
DOI: 10.1186/s12871-019-0794-7
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycemia reduces the shivering threshold in rabbits

Abstract: Background We previously reported that each 100 mg dL − 1 reduction in blood glucose over the range from ≈90 to > 300 mg dL − 1 decreases the shivering threshold (triggering core temperature) in rabbits by 1 °C. However, the effects of lower blood glucose concentrations has yet to be evaluated. We thus evaluated the relationship between the shivering threshold and blood glucose concentration over the mild-to-severe hypoglycemic range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Shivering is uncomfortable for patients, might impair monitoring techniques, and might increase risk of complications (Lopez, 2018). Strenuous shivering can triple oxygen consumption and increase production of carbon dioxide, which might result in demand ischemia in patients with limited pulmonary or cardiac reservation (Kang et al, 2019;Wada et al, 2019). Prevention of intra-and post operation shivering is of great importance to the elderly, especially elderly patients with reduced cardiopulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Shivering is uncomfortable for patients, might impair monitoring techniques, and might increase risk of complications (Lopez, 2018). Strenuous shivering can triple oxygen consumption and increase production of carbon dioxide, which might result in demand ischemia in patients with limited pulmonary or cardiac reservation (Kang et al, 2019;Wada et al, 2019). Prevention of intra-and post operation shivering is of great importance to the elderly, especially elderly patients with reduced cardiopulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…A catheter was inserted into the femoral artery to measure the mean arterial pressure (MAP) and for blood sampling. Rectal temperature was monitored constantly and maintained at 39 ℃ ± 1 ℃ with a heating blanket because the normal temperature of Japanese White rabbits has been reported to be around 39 ℃ [ 17 , 18 ]. After the experiment, the rabbits were sedated with 100 mg/kg of pentobarbital sodium and euthanized via an intravenous injection of 10 mL of potassium chloride (2 mEq/mL).…”
Section: Methodsmentioning
confidence: 99%
“…For New Zealand White rabbits, whole-blood and plasma glucose levels range between 3.7 and 10.2 mmol/L, with whole-blood glucose levels generally lower than plasma levels (as reviewed in [29,30]). In Japanese White rabbits, some authors have reported blood glucose values between 5.6 and 7.8 mmol/L [31]. However, it is important to note that factors other than diabetes can also influence blood glucose levels, such as stress [29].…”
Section: Gestational Diabetesmentioning
confidence: 99%